Development of Articulation Screening Tool to Assess the Articulation Errors in Urdu Speaking School Going Children - Hamda Muzaffar; Nayab Iftikhar; Muhammad Sikander Ghayas Khan; Sumera Nawaz Malik (University of Management and Technology, 2019)
Urdu is the national language of Pakistan and more than 100 million people speak Urdu worldwide. Urdu has 43 phonemes, however, there are some distinct phonemes in English and Urdu languages that affect the accuracy of test results. Ultimately, it leads to difficulty in assessment, diagnosis and intervention planning. This study is aimed to develop a criterion based articulation screening tool to identify articulation errors in Urdu speaking school going children. For this purpose, 500 Urdu words were selected after literature review for eliciting spontaneous single word responses at initial, medial and final positions. 10 professionals were requested to review and rate each word on a scale ranging from 1 - 5 (1=strongly disagree, 2= disagree, 3= neutral, 4=agree, 5= strongly agree). Pilot study was conducted on 25 Urdu speaking school going children to check content validity. The mean score of all the responses was calculated and the top three responses were selected for further application. In the second application, 200 school going children including 100 boys and 100 girls were included. Their responses comprising sound utterances at initial, medial and final positions were converted to mean scores. Mean scores of expert opinion, pilot study and final application of UAST were calculated using Excel spreadsheets. The minimum mean score of selected words was 3, whereas the maximum mean score was 5. Final application proves the validity of UAST. The minimum mean score of selected words was 4.5, whereas the maximum mean score was 5. The study proved that UAST is a valid screening tool to screen articulation errors in Urdu speaking school going children.